Myrosinase-dependent and –independent formation and control of isothiocyanate products of glucosinolate hydrolysis - Angelino, Donato; Dosz, Edward B.; Sun, Jianghao; Hoeflinger, Jennifer L.; Van Tassell, Maxwell L.; Chen, Pei; Harnly, James M.; Miller, Michael J.; Jeffery, Elizabeth H. (Frontiers in Plant Science, 2015)
Brassicales contain a myrosinase enzyme that hydrolyzes glucosinolates to form toxic isothiocyanates, as a defense against bacteria, fungi, insects and herbivores including man. Low levels of isothiocyanates trigger a host defense system in mammals that protects them against chronic diseases. Because humans typically cook their brassica vegetables, destroying myrosinase, there is a great interest in determining how human microbiota can hydrolyze glucosinolates and release them, to provide the health benefits of isothiocyanates. Isothiocyanates are highly reactive electrophiles, binding reversibly to thiols, but accumulating and causing damage when free thiols are not available. We found that addition of excess thiols released protein-thiol-bound isothiocyanates, but that the microbiome supports only poor hydrolysis unless exposed to dietary glucosinolates for a period of days. These findings explain why 3 – 5 servings a week of brassica vegetables may provide health effects, even if they are cooked.